Q: 5.2y plus 5.2y plus y-1 plus y-1 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is linear. The highest power is 1 (x = x1, y = y1) so it is linear.

false

Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4

Press the Y= button and type 'X+2' (not the quotes) next to Y1 (or any other Y will work). Then press GRAPH. (To type X, press the X,T,θ,n button. If you don't see Y1= when you press Y=, press MODE and select FUNC, then try again.)

X , y1 , -92 , -133 , -17

Related questions

It is linear. The highest power is 1 (x = x1, y = y1) so it is linear.

false

It is not possible to give a sensible answer because the operator between y1 and 9x is not visible.

It's m = y2 - y1/ x2- x1 It's m equals y2 minus y1 over x2 minus x1

Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4

Unfortunately, limitations of the browser that is used by WA means that most symbols cannot be seen. Please resubmit using words like "plus", "minus" and "equals".

It is false-apex

Press the Y= button and type 'X+2' (not the quotes) next to Y1 (or any other Y will work). Then press GRAPH. (To type X, press the X,T,θ,n button. If you don't see Y1= when you press Y=, press MODE and select FUNC, then try again.)

formula for the midpoint of a line

X , y1 , -92 , -133 , -17

m is the slope of the line; that is, the change in y divided by the change in x

Let P(x1, y1), Q(x2, y2), and M(x3, y3).If M is the midpoint of PQ, then,(x3, y3) = [(x1 + x2)/2, (y1 + y2)/2]We need to verify that,âˆš[[(x1 + x2)/2 - x1]^2 + [(y1 + y2)/2 - y1]^2] = âˆš[[x2 - (x1 + x2)/2]^2 + [y2 - (y1 + y2)/2]^2]]Let's work separately in both sides. Left side:âˆš[[(x1 + x2)/2 - x1]^2 + [(y1 + y2)/2 - y1]^2]= âˆš[[(x1/2 + x2/2)]^2 - (2)(x1)[(x1/2 + x2/2)) + x1^2] + [(y1/2 + y2/2)]^2 - (2)(y1)[(y1/2 + y2/2)] + y1^2]]= âˆš[[(x1)^2]/4 + [(x1)(x2)]/2 + [(x2)^2]/4 - (x1)^2 - (x1)(x2) + (x1)^2 +[(y1)^2]/4 + [(y1)(y2)]/2 + [(y2)^2]/4 - (y1)^2 - (y1)(y2) + (y1)^2]]= âˆš[[(x1)^2]/4 - [(x1)(x2)]/2 + [(x2)^2]/4 + [(y1)^2]/4 - [(y1)(y2)]/2 + [(y2)^2]/4]]Right side:âˆš[[x2 - (x1 + x2)/2]^2 + [y2 - (y1 + y2)/2]^2]]= âˆš[[(x2)^2 - (2)(x2)[(x1/2 + x2/2)] + [(x1/2 + x2/2)]^2 + [(y2)^2 - (2)(y2)[(y1/2 + y2/2)] + [(y1/2 + y2/2)]^2]]= âˆš[[(x2)^2 - (x1)(x2) - (x2)^2 + [(x1)^2]/4 + [(x1)(x2)]/2 + [(x2)^2]/4 + (y2)^2 - (y1)[(y2) - (y2)^2 + [(y1)^2]/4) + [(y1)(y2)]/2 + [(y2)^2]/4]]= âˆš[[(x1)^2]/4 - [(x1)(x2)]/2 + [(x2)^2]/4 + [(y1)^2]/4 - [(y1)(y2)]/2 + [(y2)^2]/4]]Since the left and right sides are equals, the identity is true. Thus, the length of PM equals the length of MQ. As the result, M is the midpoint of PQ